EGFR mutations and high PD-L1 expression of lung squamous cell carcinoma patients achieving pCR following neoadjuvant immuno-chemotherapy: Case report - Xu, Xiangyu; Shi, Zixia; Fu, Dan; Huang, Depei; Ma, Zheng (Frontiers in Oncology, 2022)
The treatment of lung cancer has fully entered the era of immunotherapy, which has significantly elevated the survival rate of patients with advanced non-small cell lung cancer (NSCLC), thus shedding light on resectable NSCLC. Previous clinical trial data suggested that neoadjuvant immuno-chemotherapy obtained a significant objective response rate (ORR) and disease control rate (DCR). Here, a case that achieved an excellent outcome following neoadjuvant immuno-chemotherapy was reported. The patient admitted to our hospital was 58 years old, female, with a rare case of stage IB lung squamous cell carcinoma (LUSC) harboring both epidermal growth factor receptor (EGFR) p.L858R mutations and high expression of programmed death ligand-1 (PD-L1) (tumor proportion score (TPS)=80%). Her tumor substantially shrunk following two cycles of neoadjuvant immuno-chemotherapy. The patient successively received single-port right upper thoracoscopic lobectomy + mediastinal lymph node dissection, which attained pathologic complete response (pCR). Additionally, the patient had grade 2 myelosuppression during the two cycles, which was treated with polyethylene glycol recombinant human granulocyte colony-stimulating factor (rhG-CSF). The patient was discharged uneventfully without any procedure-related complications. Two courses of adjuvant immuno-chemotherapy were administered postoperatively, leaving the patient in good physical condition at the 5-month follow-up visit. This case provided evidence for the feasibility and effectiveness of neoadjuvant immuno-chemotherapy in treating early-stage LUSC with EGFR mutations and high expression of PD-L1. However, randomized and multi-center controlled trials are required to validate the findings.